Economic Load Dispatch with Valve-point Effect Using Bacterial Foraging Algorithm - Muhammad Ridha Fauzi; Rahmad Al Rian (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Fuel is the most cost component of thermal power generation. The output power of each plant should not exceed the needs of the consumer's load. Unoptimal generation between generating units can cause power losses along the transmission line so that the fuel drain is large enough. The purpose of this study was to determine the optimal power output combination of each generating unit and determine the minimum total fuel cost of the combined power output of the plant by taking into account the valve-point effect and the operational constraint (economic load dispatch). The Newton-Raphson method is used to calculate the transmission line power losses. In this research, Bacterial Foraging Algorithm (BFA) optimization method is proposed to solve the problem of economic load dispatch. This method uses natural selection of optimum global bacterium which has a good food search strategy in the fitness function. The effectiveness of BFAs is tested on IEEE 5 bus 3 generatorsystem and IEEE 30 bus 6 generator system. The results of this proposed method show the optimal value of both generating systems.